Jab tak hai jaan a Yash Chopra Romance - Chopra, Yash 1932-2012; Chopra, Aditya 1971-; Khan, Shah Rukh 1965-; Kaif, Katrina 1984-; Sharma, Anushka 1988- (Yash Raj, 2012)
Through a personal diary account a carefree media professional discovers that a Indian Army man who fascinates her has a love interest tucked away in London. Will she be able to bridge the gap and get close to him? Or will his past come back to haunt?
Disc 2 special Features : Making of the film -- Making of the songs -- Deleted scenes -- Shahrukh Khan learns to play the guitar for challa -- Shahrukh Khan bikes through Ladakh -- Theatrical trailer & promos. - Disc 3 special features : Yash Chopra in conversation with Shahrukh Khan -- JTHJ premiere at YRF studios, Mumbai. - DVD; NTSC, all regions; anamorphic widescreen; Dolby digital
Shahrukh Khan, Katrina Kaif, Anushka Sharma
Music, A R Rahman ; lyrics, Gulzar
Keywords: India / Army / Drama; Diaries / Drama; Triangles (Interpersonal relations) / Drama; Indien; Tagebuch